Kurikulum Pendidikan Agama Islam Di Sekolah Dan Madrasah (Studi Kasus Di MA Dan SMK Miftahul Ulum Panyeppen Pamekasan) - Khoirul Anam; Maimun Maimun (Journal on Education, 2024)
Islamic Religious Education (PAI) in Indonesia has an important role in molding the character and morals of students, especially in secondary education environments such as Madrasah Aliyah (MA) and Vocational High Schools (SMK). This research was conducted to analyze the differences and similarities in the PAI curriculum in MA and SMK under the Miftahul Ulum Panyepen Islamic Boarding School, one of the oldest Islamic boarding schools in Pamekasan, East Java. The research method chosen was a qualitative approach using data collection techniques through direct observation, in-depth interviews and document analysis. The research results show that the PAI curriculum at MA Miftahul Ulum is more in-depth and focuses on comprehensive religious teaching, including the study of the Al-Qur'an, Hadith, Fiqh and Morals. Meanwhile, the PAI curriculum at Miftahul Ulum Vocational School is more integrated with vocational and vocational education, with a focus on applying Islamic values ​​in the context of the world of work. Even though there are differences in focus, both of them emphasize the importance of religious values ​​in forming students' character. This research provides deeper insight into the dynamics of the PAI curriculum at both institutions and how it contributes to students' academic and spiritual development. It is hoped that the results can become a reference for developing PAI curricula in other educational institutions in Indonesia.